Role Reversals and Permeable Bodies in the Modern Robinsonade: From Postcolonialism to Ecocriticism - Gill, Patrick (Nordic Journal of English Studies, 2024)
This essay argues that the particular lens of Bakhtinian body theory as developed for the Robinsonade by Rebecca Weaver-Hightower will help to shed light on a process observable over the past fifty years, in which colonial and postcolonial authors first embraced and then quickly abandoned the technique of role reversal in drafting their castaway stories. Enamoured of its comedic potential, Adrian Mitchell wrote Man Friday (1973). Derek Walcott was somewhat more circumspect in his Pantomime (1978), based on the realisation that role reversal demands the ascription of univocal roles and identities, something he did not see in evidence in the creolised world of the Caribbean. Later colonial and postcolonial writers such as J. M. Coetzee and Patrick Chamoiseau were then at pains to avoid questions of identity altogether, making epistemology and discourse their preferred topics. By the beginning of the twenty-first century, however, the clichéd identities formerly applied to Indigenous peoples (physical strength, close connection to nature) could be brought to bear on the idea of nature itself, thus making animal Robinsonades such as Life of Pi (2001) and The Red Turtle (2016) tremendous successes that could forgo the messiness of human affairs and simply champion the everlasting superiority of nature over civilisation as an expression of contemporary environmental preoccupations.